An analysis of whether Pillar Three of the Responsibility to Protect doctrine obliges the Security Council to act in cases of mass atrocities such as those in Syria - Tladi, Dire (University of Pretoria, 2016)
Mini Dissertation (LLM)--University of Pretoria, 2015.